Analisis Tingkat Kepatuhan Wajib Pajak Sebelum, Saat, dan Sesudah Pandemi Covid-19 (Studi Pembayaran Pajak Bumi dan Bangunan Tahun 2019-2024 Di Bandar Lampung) - Julia Wulandari; Nana Mulyana; Eko Budi Sulistio (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2026)
Land and Building Tax (PBB) is a potential source of tax in Regional Original Income (PAD), however its revenue realization remains suboptimal, resulting in increasing tax arrears. This condition is influenced by low tax awareness and the deterioration of economic conditions during the Covid-19 pandemic, which affected taxpayers ability to pay. In response, the local government implemented a fiscal policy in the form of PBB tax rate reductions. This study aims to analyze differences in the compliance levels of taxpayers receiving PBB tax reductions during the period 2019–2024, covering the pre-pandemic, pandemic, and post-pandemic periods in Sukarame District, Bandar Lampung City. This research employs a descriptive comparative design with a quantitative approach, utilizing a paired sample t-test as well as analyses of ability to pay tax and willingness to pay tax. The results indicate significant differences in taxpayer compliance across periods, with an overall declining trend. However, no significant difference was found between the pre-pandemic and pandemic periods (2022) due to similar payment patterns. Although taxpayers’ ability to pay has gradually improved, compliance levels remain fluctuating and stagnant. This stagnation is influenced by suboptimal willingness to pay, low perceived consequences of late payments due to repeated penalty waivers, variations in incentive schemes, limited policy socialization, and payment system preferences. Therefore, improving PBB compliance requires policy strategies that emphasize strengthening tax awareness and ensuring consistent enforcement of tax obligation.